Cytomorphological Spectrum of Breast Fine Needle Aspiration Cytology Using International Academy Cytology Yokohama System- A Retrospective Study in the Tertiary Care Center of Sahiwal: Cytomorphological Spectrum of Breast Fine Needle Aspiration Cytology - Lail, Raees Abbas; Tahir, Qurrat Ul Ain; Shafique, Sadaf; Shamsi, Farwa Batool; Waqas, Omer; Shams, Muhammad Usman (Pakistan Journal of Health Sciences, 2025)
Breast carcinoma is also a very widespread and upsetting cancer that pertains to women, and the incidence of the same is also high in developing countries. Breast cancer is one of the most common malignancies women are exposed to, and its occurrence is particularly high in third-world countries. Fine needle aspiration cytology (FNAC) is a good diagnostic tool when it comes to the detection of early breast lesions. Objectives: To evaluate the role of FNAC in the screening and assessment of breast lumps to identify breast cancer in the resource-poor Sahiwal Division. Methods: This retrospective cross-sectional study included 392 females presenting with palpable breast lumps. After obtaining informed consent, FNAC was performed, and the aspirated material was used to prepare and stain slides for cytological examination. The data were collected from clinical records and then analyzed. Results: Out of 392 female patients, the majority of breast lesions (40.05%) were found in C5; malignant category followed by 26.78% in C2(benign), 21.93% of lesions in C3 (atypical), and 10.52% in C4 (suspicious for malignancy) categories. Most of the patients (39.84%) were aged 41 and above, and 143 patients (36.48%) were seen in category 5whereas the duration of lesion according to history of disease for the majority of cases (36.48%) can be seen from 7 to 12 months in reporting category 5 (40.86%). Conclusions: The fine needle aspiration cytology (FNAC) is associated with fast, trustworthy, and economical means of initial classification of palpable breast growths on the basis of the standardized IAC system.